2020
DOI: 10.24018/ejfood.2020.2.4.65
|View full text |Cite
|
Sign up to set email alerts
|

Proximate, Microbial and Sensory Characteristics of Cowpea Milk Fermented with Probiotic Starter Cultures

Abstract: Fermentation of cowpea milk was carried out using three mixed starter cultures containing (i) Lactobacillus acidophilus, Bifidobacterium spp, and Streptococcus thermophilus (ABT) (ii) Lactobacillus delbrueckii subsp. bulgaricus and Streptococcus thermophilus (DT) or (iii) Lactobacillus rhamnosus GR-1 and Streptococcus thermophilus (GT). Proximate composition of raw and fermented cowpea milk was determined using the AOAC methods. Lactic acid bacteria survival and sensory attributes of the fermented cowpea milk … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…Even though the preparation of legume-based water extracts can be carried out following different protocols, we can conclude that lactic acid bacteria are able to ferment legume extracts and survive in these beverages during cold storage, as also demonstrated for the strains Lacticaseibacillus rhamnosus GR-1 and Streptococcus thermophilus found in cowpea beverages after 28 days [ 44 ].…”
Section: Resultsmentioning
confidence: 93%
“…Even though the preparation of legume-based water extracts can be carried out following different protocols, we can conclude that lactic acid bacteria are able to ferment legume extracts and survive in these beverages during cold storage, as also demonstrated for the strains Lacticaseibacillus rhamnosus GR-1 and Streptococcus thermophilus found in cowpea beverages after 28 days [ 44 ].…”
Section: Resultsmentioning
confidence: 93%
“…Consequently, during fermentation, some of the lipids might have been utilised by the starter culture to yield energy [10]. Also, Aduol et al [27] reported a significant difference (p < 0.05) in the low crude fat content (0.3-0.5%) in fermented cowpeas milk Yoba Fiti GR-1 culture. e fat content observed in the fermented cowpea-peanut milk is beneficial to human health since it is within the recommended dietary intake level range for fat by the U.S. Department of Health and Human Services and U.S. Department of Agriculture Report of 2015.…”
Section: Chemical Characteristics Of the Fermented Peanut-cowpea Milkmentioning
confidence: 99%
“…Plant matrices are a good carrier for probiotic bacteria. Products made by plant fermentation with probiotics can meet consumers' demands for health-promoting, dairy-free products [129,[197][198][199][200]. Most of the plant-based beverages described in the literature are fermented using Lactobacillus, Streptococcus, and Bifidobacterium [24,129,194,201].…”
Section: Fermentation Of Legume-based Beverages Using Labmentioning
confidence: 99%
“…The cowpea-based beverage turned out to be a good fermentation matrix using probiotic cultures containing bacteria from the genera Lactobacillus, Bifidobacterium, and Streptococcus [198]. The obtained fermented beverage showed faster microbial growth during the first two weeks of storage.…”
Section: Fermentation Of Legume-based Beverages Using Labmentioning
confidence: 99%